FRI0165 Relationship Between Serum Concentrations of Cytokines and Disease Activity in Rheumatoid Arthritis Patients Treated with Tocilizumab. (9th June 2015) - Mitsui, H.; Yoshikawa, K.; Nagaya, Y.; Otsuka, T.; Mitsui, T.
Abstract : Background: The balance between T type 17 cells (Th17) and regulatory T cells (Treg) affects inflammation in RA pathogenesis, and both subpopulations depend on transforming growth factor (TGF)-b for their induction, but the presence of interleukin (IL)-6 disturbs this balance and induction of T17 may be increased. Objectives: The aim of the present study was to investigate changes in serum concentrations of cytokines such as IL-6, IL-17, tumor necrosis factor (TNF)-a and TGF-b in patients treating with tocilizumab (TCZ), an IL-6 receptor antibody, before and after treatment. Methods: Participants comprised 31 patients (23 women, 8 men) who met the 2010 ACR/EULAR classification criteria. At baseline and at weeks 24 and 52 of TCZ treatment, clinical results were obtained from clinical records and evaluations were made using the 28-joint disease activity score (DAS28-ESR). Peripheral blood was obtained at the same time and serum concentrations of cytokines were analyzed. Results: Thirty patients received follow-up, and 3 patients ceased TCZ therapy because of side effects. DAS28-ESR scores decreased from 5.09 at baseline, to 2.95 in Week 24 and 2.66 in Week 52. The number of good responders was 17 in week 24, and 19 in week 52, compared to 9 moderate responders in week 24, and 7 in week 52, and 2 non-responders in week 24, and 1 in week 52, according to the clinical evaluation criteria of EULAR. Twelve patients were in remission state (DAS28-ESR) at week 56. Mean concentration of serum IL-6 was 19.8 (pg/ml) at baseline and 30.2 (pg/ml) at week 56 in good responders at week 56 (Group A), compared to 45.0 (pg/ml) at baseline and 73.6 (pg/ml) at week 56 in moderate responders at week 56 (Group B). Mean serum concentration of TNF-a was 18.6 (pg/ml) at baseline and 10.4 (pg/ml) at week 56 in Group A, and 12.6 (pg/ml) and 12.9 (pg/ml) in Group B. Mean serum concentration of TGF-β in group A was 34.8 (ng/ml) at baseline and 30.6 (ng/ml) at 56 weeks in Group A, and 37.7 (ng/ml) and 31.5 (ng/ml) in Group B. Mean serum concentration of IL-17A was 6.08 (pg/ml) at baseline and 1.76 (pg/ml) at week 56 in Group A, and 6.56 (pg/ml) and 4.25 (pg/ml) in Group B. Mean serum concentration of TNF-α was 18.6 (pg/ml) at baseline and 10.4 (pg/ml)at week 56 in Group A, and 12.6 (pg/ml) and 12.9 (pg/ml) in Group B. Conclusions: As 63.3% of patients treated with TCZ were good responders and 44.4% of patients were in remission at week 52, the clinical effectiveness of TCZ therapy was confirmed. Comparing Groups A and B, serum IL-6 level was lower in good responders before treatment. Serum IL-6 level at baseline may reflect disease activity, and high IL-6 level at baseline may suggest poor prognosis after TCZ therapy. Otherwise, TNF-a showed no significant correlation with disease activity markers at baseline. Serum level of TNF-a at baseline may not indicate prognosis after TCZ therapy. Mean serum level of IL-17A was significantly lower in Group A at week 52. Mean serum level of TGF-b showed no significant differences among the Groups at baseline, but the reduction after TCZ therapy was smaller in Group A. This result indicates that a high concentration of serum IL-17A and a low concentration of serum TGF-b correlate with poor efficacy of TCZ therapy. Disclosure of Interest: H. Mitsui: None declared, K. Yoshikawa Shareholder of: Chugai Pharmaceutical Co., Ltd, Y. Nagaya Shareholder of: Viomet Japan, T. Otsuka: None declared, T. Mitsui: None declared